Do impulse oscillometry parameters differ between children and adolescents with symptoms of rhinitis and those without? - Juliana Cardoso; Bianca Kons dos Santos; Luana Vincensi Dorigo; Renata Maba Gonçalves Wamosy; Bianca Dana Horongozo Itaborahy; Camila Isabel Santos Schivinski (Jornal Brasileiro de Pneumologia, 2022)
ABSTRACT Objective: To compare impulse oscillometry parameters between healthy children and adolescents with symptoms of rhinitis and those without. Methods: This was a cross-sectional analytical study of healthy individuals 7-14 years of age. Health status was determined through the use of questionnaires. We performed anthropometric measurements, impulse oscillometry, and spirometry. Results: The sample comprised 62 students, with a mean age of 9.58 ± 2.08 years and a mean body mass index (BMI) of 17.96 ± 3.10 kg/m2. The students were divided into two groups: those with symptoms of rhinitis (n = 29) and those without such symptoms (n = 33). The oscillometry results and anthropometric parameters were normal in both groups and did not differ significantly between the two. The variables age, height, and body mass, respectively, correlated negatively and moderately with most of the following parameters: total airway resistance (r = −0.529, r = −0.548, and r = −0.433); central airway resistance (r = −0.441, r = −0.468, and r = −0.439); respiratory impedance (r = −0.549, r = −0.567, and r = −0.455); reactance at 5 Hz (r = 0.506, r = −0.525, and r = −0.414); reactance area (r = −0.459, r = −0.471, and r = −0.358); and resonance frequency (r = −0.353, r = −0.371, and r = −0.293). We found that BMI did not correlate significantly with any of the parameters evaluated. The same was true when we analyzed each group in isolation. Conclusions: In our sample, impulse oscillometry parameters did not differ between the students who had symptoms of rhinitis and those who did not.